Prematurity due to maternal brucella infection and review of the literature - Aydın, Banu; Beken, Serdar; Akansel, Ragıp; Dilli, Dilek; Okumuş, Nurullah; Zenciroğlu, Ayşegül; Tanır, Gönül (The Turkish Journal of Pediatrics, 2013)
Brucellosis is a zoonosis caused by ingestion of unpasteurized milk or other dairy products from infected animals or through close contact with their secretions. Human-to-human transmission, which is rare, has been reported in association with blood transfusion, bone marrow transplantation, transplacental or perinatal exposure, and breastfeeding. In the neonatal period, congenital brucellosis, which is an extremely rare condition, can lead to serious clinical consequences with a high morbidity and mortality rate. The case presented here is a premature baby born at 25 weeks’ gestation to a mother suffering from severe oligohydramnios, premature rupture of membranes and untreated acute brucellosis. The baby had severe respiratory distress and radiological findings compatible with pulmonary infection. The blood cultures of the baby and the mother were positive for Brucella melitensis, supporting the diagnosis of brucellosis with presumed transplacental transmission.